Quantitative Risk Assessment in Life, Health and Pension Insurance - Bacinello, Anna (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The high volatility in financial markets, together with the ultra-low interest rate environment and increased life expectancy, constitute serious threats for providers of long-term investment guarantees and lifelong benefits. Even if the COVID-19 pandemic is currently causing a mortality shock, its influence on future mortality is not clear and one possible scenario could be a further increase in the life expectancy of survivors. The risk involved with all of these "exogenous" factors is amplified by the uncertainty characterizing individuals' behavior when making decisions concerning, e.g., surrender, partial withdrawals, annuitization, etc. This special issue aims at contributing to the study of suitable solutions allowing to build resilience against various risks that impact on life, health and pension insurance portfolios. In particular, it collects five high-quality research papers analysing theoretical or practical aspects related to the following topics: Design of new pension insurance products and risk-management of loan insurance; Assessing capital requirements for demographic risk in a life insurance portfolio - Stochastic models and numerical techniques; Analysis and risk-management of the long-run impact of COVID-19 on the life insurance business.